Economists vs. Engineers—Assessing Students’ Entrepreneurial Intentions from the Perspective of Mindset and Resilience - Mihaela Brindusa Tudose; Raluca Petronela Lazarescu; Raluca Irina Clipa (Administrative Sciences)
Given that student entrepreneurship contributes to the intensification of economic activities and the improvement of the social well-being of the parties involved, evaluating and fostering students’ entrepreneurial intentions can be a step in moving from intention to action in the entrepreneurial process. From this perspective, the present study assesses students’ entrepreneurial intentions and measures the impact of the most important determinants based on online questionnaires addressed to students from two different fields of study: economics and engineering. Using the collected data (N = 392 students) and analysis methods based on correlation and stratified multiple regression as well as non-parametric tests (Mann–Whitney U), the study reveals that students’ entrepreneurial intentions are influenced by mindset and resilience. The study indicates that the influences can vary significantly when the analyses include control variables, such as gender, field of study, year of study, professional experience, age, and country of origin. It is also important to note that the statistical significance of the results regarding the impact of resilience varies depending on the specifics of the control variables. This study considered both analyses of resilience (as a synthetic indicator) and its subcomponents. The results of this study have both theoretical and practical utility.